The Functional Role of Voltage-Gated Sodium Channel Nav1.5 in Metastatic Breast Cancer - Luo, Qianxuan; Wu, Ting; Wu, Wenfang; Chen, Gong; Luo, Xuan; Jiang, Liping; Tao, Huai; Rong, Mingqiang; Kang, Shuntong; Deng, Meichun (Frontiers in Pharmacology, 2020)
Voltage-gated sodium channels (VGSCs), which are abnormally expressed in various types of cancers such as breast cancer, prostate cancer, lung cancer, and cervical cancer, are involved in the metastatic process of invasion and migration. Nav1.5 is a pore-forming α subunit of VGSC encoded by SCN5A. Various studies have demonstrated that Nav1.5, often as its neonatal splice form, is highly expressed in metastatic breast cancer cells. Abnormal activation and expression of Nav1.5 trigger a variety of cellular mechanisms, including changing H+ efflux, promoting epithelial-to-mesenchymal transition (EMT) and the expression of cysteine cathepsin, to potentiate the metastasis and invasiveness of breast cancer cells in vitro and in vivo. Here, we systematically review the latest available data on the pro-metastatic effect of Nav1.5 and its underlying mechanisms in breast cancer. We summarize the factors affecting Nav1.5 expression in breast cancer cells, and discuss the potential of Nav1.5 blockers serving as candidates for breast cancer treatment.